2017
DOI: 10.17159/2078-516x/2017/v29i1a3438
|View full text |Cite
|
Sign up to set email alerts
|

A 12-week primary prevention programme and its effect on health outcomes (the Sweet Hearts biokinetics pilot study)

Abstract: Background: The prevalence of non-communicable diseases (NCDs) and physical inactivity are concerning within the South African population. To address these concerns, the ‘Strategic Plan for Prevention and Control of NCDs 2013-2017’ was developed. In response to this plan, a 12-week pilot biokinetics community health programme, Sweet Hearts, was initiated. Methods: This study is a prospective pilot study evaluating the feasibility and effectiveness of the intervention. Twenty- five individuals participated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The present study's protocol and results have been reported previously. (13) This paper's results will focus solely on the Stroop Task. Participants performed the Stroop cognitive task on a Figure 1).…”
Section: Measurementsmentioning
confidence: 99%
“…The present study's protocol and results have been reported previously. (13) This paper's results will focus solely on the Stroop Task. Participants performed the Stroop cognitive task on a Figure 1).…”
Section: Measurementsmentioning
confidence: 99%